War Diary of 1st Battalion Canadian Scottish Regiment, Vol. 60 - Appendix 07 - Canada. Canadian Army. Canadian Scottish Regiment (Princess Mary's) (1944)
This appendix consists of a report on "D" Company's experiences in the Battle of Cussy and for Hill 168 near Falaise, France.